Prognostic influence of Korean public medical insurance system on breast cancer patients - Hwang, Ki-Tae (Ann Surg Treat Res, 2019)
PURPOSE: To investigate the prognostic influence of Korean public medical insurance system on breast cancer patients. METHODS: Data of 1,068 patients with primary invasive breast cancer were analyzed. Korean public medical insurance status was classified into 2 groups: National Health Insurance and Medical Aid. Kaplan-Meier estimator and Cox proportional hazards model were used for survival analysis. RESULTS: The Medical Aid group showed worse prognoses compared to the National Health Insurance group both in overall survival (P = 0.001) and recurrence-free survival (P = 0.006). The Medical Aid group showed higher proportion of patients with tumor size > 2 cm (P = 0.022), more advanced stage (P = 0.039), age > 50 years (P = 0.003), and low education level (P = 0.003). The Medical Aid group showed higher proportion of patients who received mastectomy (P < 0.001) and those who received no radiation therapy (P = 0.013). The Medical Aid group showed a higher rate of distant recurrence (P = 0.014) and worse prognosis for the triple negative subtype (P = 0.006). Medical insurance status was a significant independent prognostic factor in both univariate analysis and multivariate analysis. CONCLUSION: The Medical Aid group had worse prognosis compared to the National Health Insurance group. Medical insurance status was a strong independent prognostic factor in breast cancer. Unfavorable clinicopathologic features could explain the worse prognosis for the Medical Aid group. Careful consideration should be given to medical insurance status as one of important prognostic factors for breast cancer patients.